Analysis of Gender, Age, and Grade Difference on Fomo Score: Study at SMA (SLUA) Saraswati 1 Denpasar - I Nyoman Gede Semarajana; Anak Agung Dwi Ratih Arningsih; I Gede Jenstin Prana Arsana (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
Fear of Missing Out (FoMO) is an increasingly relevant psychological phenomenon for high school students due to the increasing use of social media and social pressure to stay connected. This study aims to investigate the variation of FoMO levels in Saraswati 1 Denpasar High School students by considering demographic factors such as gender, age, and class. Using a cross-sectional descriptive quantitative design, data were collected from 236 students through a FoMO Scale-based questionnaire by Przybylski et al. (2013). The results showed that 40.7% of the students experienced FoMO at a moderate level, with no statistical analysis finding any significant differences based on sex (p = 0.364), age (p = 0.643), or class (p = 0.174). These findings indicate that demographic factors may not be the main factor influencing FoMO levels in this population. This study highlights the need for further exploration of the psychosocial factors that contribute to FoMO, including the influence of social media, peer pressure, and students' emotional regulation. In addition, future research may explore school-based intervention strategies to reduce the impact of FoMO on mental health, such as digital literacy programs and psychological support to improve students' emotional well-being. As such, these findings could provide insights for schools and mental health practitioners in designing more effective approaches to help students manage FoMO and its impacts.